THE EFFECT OF ADDRESSING ATTRACTION, PRICE PERCEPTION AND ELECTRONIC WORD OF MOUTH (EWOM) ON THE PURCHASE DECISION OF YOU BRAND COSMETICS - Julianti Cristimonica; Mulyo Budi Setiawan (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2022)
This study examines the effect of advertising attractiveness, price perception, and electronic word of mouth (ewom) on the purchasing decision of YOU . brand cosmetics This research was conducted at the Balqis Cosmetics Shop in the city of Limpung. The population in this study were consumers who had bought YOU cosmetic products at the Balqis Kosmetik store and the sample was set at 100 respondents. Primary data was obtained by using a questionnaire through the media google form. Answer using a Likert scale from one to five. The results are all valid and reliable questions. The regression results show that the advertising attractiveness and price perception variables are positive and significant, while the electronic word of mouth (ewom) variable is negative and insignificant. Based on the results of the model test, the three independent variables were only able to explain 48.5 percent of the purchase decision.